2021
DOI: 10.1186/s12872-021-02288-9
|View full text |Cite
|
Sign up to set email alerts
|

Obesity measures, metabolic health and their association with 15-year all-cause and cardiovascular mortality in the SAMINOR 1 Survey: a population-based cohort study

Abstract: Background The mortality of metabolic-obesity phenotypes has been thoroughly studied, but it is not known if or how the association between mortality and body mass index (BMI), waist circumference or a body shape index (ABSI) differ in strata of cardiometabolic health status. Methods We linked data on 12,815 men and women aged 36–79 years from the SAMINOR 1 Survey with mortality data from the Norwegian Cause of Death Registry. We defined metabolica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…To the best of our knowledge, this study is the first to examine the relationship between obesity severity and CVD risk by metabolic status in participants with obesity. One recent study evaluated the association between BMI and CVD mortality by metabolic status 34 . They conducted analyses among adults with general BMI levels stratified by metabolic status (healthy/unhealthy), taking participants with obesity as a group without considering obesity severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this study is the first to examine the relationship between obesity severity and CVD risk by metabolic status in participants with obesity. One recent study evaluated the association between BMI and CVD mortality by metabolic status 34 . They conducted analyses among adults with general BMI levels stratified by metabolic status (healthy/unhealthy), taking participants with obesity as a group without considering obesity severity.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated obesity severity and BMI values were associated with a higher risk in men when compared to women in MUO, which was consistent with previous studies. 33,34 The fact that men typically have more VAT than women even with the same BMI values, might contribute to the sex difference. 32 In our study, the association significantly differed in MUO participants aged <65 years and ≥ 65 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other significant positive changes were observed in BMI, WC, DBP, FPG, TG, Chol, and HDL (except LDL). While, small in effect sizes, they may also be important findings because the normal clinical course for this patient group involves continued deterioration of the metabolic risk profile [ 47 49 ]. Thus, the 5-year PAP intervention period yielded both a treatment effect—with improved metabolic risk factors and attenuation of expected worsening of risk factors—and a potential preventive effect against future diseases and premature death.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from epidemiological studies have shown that the prevalence of MHO ranges from less than 10% to almost 50% in obese individuals according to different definitions of metabolic health and the population studied [12][13][14]. Substantially, poor metabolic health may increase mortality regardless of obesity status [15,16]. The characterization of metabolic status would allow to identify obese patients who are at higher risk of complications, since moderate weight loss can be sufficient to transition from MUO to MHO and might also lower the risk of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%